1995
DOI: 10.1006/qres.1995.1079
|View full text |Cite
|
Sign up to set email alerts
|

The GISP2 δ18O Climate Record of the Past 16,500 Years and the Role of the Sun, Ocean, and Volcanoes

Abstract: Measured 18O/16O ratios from the Greenland Ice Sheet Project 2 (GISP2) ice core extending back to 16,500 cal yr B.P. provide a continuous record of climate change since the last glaciation. High-resolution annual 18O/16O results were obtained for most of the current millennium (A.D. 818-1985) and record the Medieval Warm Period, the Little Ice Age, and a distinct 11-yr 18O/16O cycle. Volcanic aerosols depress central Greenland annual temperature (∼1.5°C maximally) and annual 18O/16O for about 4 yr after each m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
593
3
9

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 938 publications
(653 citation statements)
references
References 0 publications
48
593
3
9
Order By: Relevance
“…Over the radiocarbon calibration interval, there are generally fewer than thirty tie points correlating deep sea core ocean/climate proxies to ice core proxies, thereby assigning calendar age estimates to most calibration points by interpolation. Differences between the various Greenland ice core chronologies are due to age model assumptions, inherent subjectivity in discerning annual bands in ice or layered sediments in general, the fidelity of proxies to record an annual signal, occasional wind erosion or scouring of some snow layers, and compacting and degrading annual signals deeper in the ice cores (Dansgaard et al, 1989(Dansgaard et al, , 1993Johnsen et al, 1992Johnsen et al, , 1995Johnsen et al, , 1997Johnsen et al, , 2001Meese et al, 1994Meese et al, , 1997Taylor et al, 1993;Stuiver et al, 1995;Andersen et al, 2004). Intervals where the annual signal is weak or missing entirely would not be counted by any of the proxies and therefore not included in Meese et al's (1997) error assessment.…”
Section: Radiocarbon Age Calibrationmentioning
confidence: 99%
“…Over the radiocarbon calibration interval, there are generally fewer than thirty tie points correlating deep sea core ocean/climate proxies to ice core proxies, thereby assigning calendar age estimates to most calibration points by interpolation. Differences between the various Greenland ice core chronologies are due to age model assumptions, inherent subjectivity in discerning annual bands in ice or layered sediments in general, the fidelity of proxies to record an annual signal, occasional wind erosion or scouring of some snow layers, and compacting and degrading annual signals deeper in the ice cores (Dansgaard et al, 1989(Dansgaard et al, , 1993Johnsen et al, 1992Johnsen et al, , 1995Johnsen et al, , 1997Johnsen et al, , 2001Meese et al, 1994Meese et al, , 1997Taylor et al, 1993;Stuiver et al, 1995;Andersen et al, 2004). Intervals where the annual signal is weak or missing entirely would not be counted by any of the proxies and therefore not included in Meese et al's (1997) error assessment.…”
Section: Radiocarbon Age Calibrationmentioning
confidence: 99%
“…Based on a marine sediment record from the Arabian Sea, the Indian monsoon varied in intra-Holocene cycles of about 1050, 1500, and 3000 years (Sirocko et al, 1996), i.e. periods similar to the climate cycles found in ice cores from Greenland (Stuiver et al, 1995;Grootes and Stuiver, 1997). One may, therefore, expect that analogous events of enhanced precipitation and fluvial runoff in South China may lead to an enlarged plume of low sea-surface salinity (SSS) offshore Hongkong ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…His analysis of varved layers from the Lake Suigetsu has demonstrated that the cooling event at approximately 11,320 B.P. (Kitagawa and van der Plicht, 1998) may corresponds with the 100 year cooling event from 11,300 to 11,400 years ago recorded in the Greenland ice core (GISP 2) (Stuiver et al, 1995).…”
Section: The Environmental Background Of the Japanese Archipelago Durmentioning
confidence: 99%
“…In correlating the oxygen isotope ratios in the GISP 2 (Stuiver et al, 1995), an abrupt increase of quartz flux that suggests the onset of dry and cold climate in inner Asia is 350 years earlier than the onset of Younger Dryas (Fukusawa, 1999: 241). This estimate is further supported by reconstructed changes in mean annual temperatures recorded in the pollen stratigraphy of Lake Suigetsu, western Japan (Nakagawa et al, 2005).…”
Section: The Environmental Background Of the Japanese Archipelago Durmentioning
confidence: 99%
See 1 more Smart Citation